Epigenetic Repression of Chloride Channel Accessory 2 Transcription in Cardiac Fibroblast: Implication in Cardiac Fibrosis - Shao, Tinghui; Xue, Yujia; Fang, Mingming (Frontiers in Cell and Developmental Biology, 2021)
Cardiac fibrosis is a key pathophysiological process that contributes to heart failure. Cardiac resident fibroblasts, exposed to various stimuli, are able to trans-differentiate into myofibroblasts and mediate the pro-fibrogenic response in the heart. The present study aims to investigate the mechanism whereby transcription of chloride channel accessory 2 (Clca2) is regulated in cardiac fibroblast and its potential implication in fibroblast-myofibroblast transition. We report that Clca2 expression was down-regulated in activated cardiac fibroblasts (myofibroblasts) compared to quiescent cardiac fibroblasts in two different animal models of cardiac fibrosis. Clca2 expression was also down-regulated by TGF-, a potent inducer of fibroblast-myofibroblast transition. TGF- repressed Clca2 expression at the transcriptional level likely via the E-box element between -516 and -224 of the Clca2 promoter. Further analysis revealed that Twist1 bound directly to the E-box element whereas Twist1 depletion abrogated TGF- induced Clca2 trans-repression. Twist1-mediated Clca2 repression was accompanied by erasure of histone H3/H4 acetylation from the Clca2 promoter. Mechanistically Twist1 interacted with HDAC1 and recruited HDAC1 to the Clca2 promoter to repress Clca2 transcription. Finally, it was observed that Clca2 over-expression attenuated whereas Clca2 knockdown enhanced fibroblast-myofibroblast transition. In conclusion, our data demonstrate that a Twist1-HDAC1 complex represses Clca2 transcription in cardiac fibroblasts, which may contribute to fibroblast-myofibroblast transition and cardiac fibrosis.